Angstrom-scale vanadium carbide rods as Pt electrocatalyst support for efficient methanol oxidation reaction. Issue 13 (14th February 2015) - Yan, Zaoxue; Gao, Lina; Zhang, Mingmei; Xie, Jimin; Chen, Min
<x xml:space="preserve">Abstract</x> Angstrom-scale vanadium carbide rods greatly increase the Pt electrocatalyst activity for methanol oxidation.